Re+e- and an effective QCD charge - Gomez, J. D.; Natale, A. A. [UNESP] (American Physical Society (APS), 2016)
We consider the electron-positron annihilation process into hadrons Re+e- up to O(αs3), and we adopt the smearing method suggest by Poggio, Quinn, and Weinberg to confront the experimental data with theory. As a theoretical model, we use a QCD coupling constant frozen in the low-energy regime, where this coupling can be parametrized in terms of an effective dynamical gluon mass (mg) which is determined through Schwinger-Dyson equations. In order to find the best fit between experimental data and theory, we perform a χ2 study, that, within the uncertainties of the approach, has a minimum value when mg/ΛQCD is in the range 1.2-1.4. These values are in agreement with other phenomenological determinations of this ratio and lead to an infrared effective charge αs(0)≈0.7. We comment how this effective charge may affect the global duality mass scale that indicates the frontier between perturbative and nonperturbative physics.